The Rhetorical and Thematic Methodology of Sheikh ‘Abdul Hayy al-Fārūqī in His Both Exegeses “Tafsīr al-Furqān fī M‘ārif al-Qurān” and “Dars-e Qurān”: A Comparative Study: أسلوب الخطاب والعناوين فى "تفسير الفرقان في معارف القرآن" و"درس قرآن" للشيخ عبدالحئ الفاروقى: دراسة مقارنة - Abbas, Kaleem; Nadeem, Dr. Muhammad Tayyeb; Chishty, Dr. Ahsanullah (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Sheikh ‘Abd al-Hayy al-Farūqī (1887-1965) was the Indo-Pak Sub-continental scholar who became famous in the scientific circles and adhered to the Sheikh of India Mahmood al-Hassan al-Deobandī and extracted the knowledge from his approach. Al-Fārūqī was among the most prominent students of Sheikh ‘Ubaidullāh al-Sindhī and Sheikh Abu al-Kalam Azad. Sheikh ‘Abdul Hayy al-Fārūqi made tremendous efforts in the liberation of the Indian subcontinent from the British rule. After completing the interpretation of the Noble Qur’an under the supervision of ‘Ubaidullāh Sindhī Al-Sindhi in the light of methodology and style of Imām Shāh Walī Allāh, he began to spread it through the teaching and the academic writings. Consequently, he wrote two Tafāsīr known as “Tafsir al-Furqan fi Ma’arif al-Qur’an” and “Dars-e Qurān”, both are in Urdu language and widely published and the first one contains two volumes and it is written for the scholars while the other one is in seven volumes where the scholar made focus on the general masses so that they can understand the true spirit of Qurān easily. This comparative study is to explore the significant features of the both exegeses which are not dealt (as per our knowledge) in an academic manner for the scholars as well for the masses.